1996
DOI: 10.1159/000237381
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Asthma Developed by Room Air Contamination with Cockroach Allergen

Abstract: To study the asthmatogenic effect of certain airborne elements of the home environment, we studied a group of guinea pigs exposed to aerosolized cockroach allergen (CRa) and side-stream cigarette (S-SC) smoke. Four groups of guinea pigs were exposed to aerosols, either saline or CRa, for 4 weeks, after a sham or S-SC smoke pretreatment. Anaphylactic antibodies were measured by passive cutaneous anaphylaxis (PCA) assay and by skin test. Animals were challenged with aerosol CRa on day 35, and lung function and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Unlike our CRa aerosol sensitization a great majority of other animal models were immunized with an allergen given intraperitoneally and often with an adjuvant [9, 10, 11, 14]. In our study the state of immunization of guinea pigs was proven by the presence of anti-CRa IgG1 [16, 17, 18] as well as by the cellularity in BAL fluid (table 1). Yet, our findings, normal contractile response to ACh and leukocytosis in BAL, closely resemble the report by Wills-Karp et al [12], whose guinea pigs were intraperitoneally immunized with OA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Unlike our CRa aerosol sensitization a great majority of other animal models were immunized with an allergen given intraperitoneally and often with an adjuvant [9, 10, 11, 14]. In our study the state of immunization of guinea pigs was proven by the presence of anti-CRa IgG1 [16, 17, 18] as well as by the cellularity in BAL fluid (table 1). Yet, our findings, normal contractile response to ACh and leukocytosis in BAL, closely resemble the report by Wills-Karp et al [12], whose guinea pigs were intraperitoneally immunized with OA.…”
Section: Discussionmentioning
confidence: 96%
“…The aerosol exposure was carried out for a period of 45 min repeated twice a day, 5 days a week, for 4 weeks. After 4 weeks of immunization, development of anaphylactic sensitivity to CRa was confirmed by both allergic skin test and PCA test as described [16, 17, 18]. Five days after the last aerosol exposure, the asthmatic responses in vivo were measured using a double chamber plethysmograph following CRa challenge (1 mg/ml × 10 ml) in conscious state as described [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental animal models, chronic coexposure to ETS increased levels of allergen-induced airway remodelling and airway responsiveness by up-regulating the expression of chemokines (Min, 2007), suggesting that ETS is a risk factor for asthma. Other studies using animal models have also reported that exposure to ETS aggravates airway allergy (Seymour, 1997(Seymour, , 2003(Seymour, , 2005Rumold, 2001), although there are also controversial reports (Kang, 1996;Boweles, 2005). In contrast, the effect of mainstream or active cigarette smoking (MTS) on asthma is controversial.…”
mentioning
confidence: 99%
“…Additional studies need to consider whether pesticide treatment for insects such as cockroaches could heighten allergenic response because cockroach antigen remains one of the most commonly reported causes of asthma (10,11). In addition, a number of cases have been reported of birth defects in children born to mothers who have previously had healthy babies.…”
mentioning
confidence: 99%